PEMBUBARAN KORPORASI: KAJIAN KOMPARATIF ANTARA SISTEM HUKUM CIVIL LAW DAN COMMON LAW - Aryadi, Arsha Medina; Hutabarat, Rugun Romaida (Legal Standing : Jurnal Ilmu Hukum, 2024)
This research analyzes the dissolution of a company as a consequence of criminal law within the framework of civil law and common law, by comparing the practice in England and Germany. The research aims to show the different approaches to company dissolution. In the UK, compulsory liquidation proceedings and administrative flexibility are prioritized to protect the interests of creditors, whereas in Germany, dissolution requires formal shareholder approval and strict administrative oversight. In addition, this study also explores the factors that influence dissolution decisions and the dispute resolution efforts that arise. Through normative research with a statutory and comparative approach, this study analyzes legal documents and regulations related to dissolution in the two selected countries. Secondary data was collected from the analysis and review of academic literature. The results show that corporate dissolution in the UK emphasizes flexibility through the Companies Act 2006 and the Insolvency Act 1986, while Germany, under the Act on Limited Liability Companies Germany, follows a strict structural process. Both prioritize creditor protection, with the duration of liquidation being shorter in the UK than Germany, which requires a minimum of one year.